The cuboctahedric Higgs oscillator from the rational Calogero model; Journal of Physics A: Mathematical and Theoretical; Vol. 40, iss. 20 - Akopyan (Hakobyan) T. S. Tigran Stepanovich (2009, 2009)
Title screen